Pengaruh Koordinasi Kerja, Komunikasi, dan Etos Kerja terhadap Kinerja Karyawan Pada PT Teknik Laut Sejahtera - Indah Kusumawati; Agus Yulistiyono; Abdul Karim Butar Butar (JUDICIOUS, 2022)
This study aims to see how much influence work coordination, communication and work ethics have on employee performance. The author conducted an analysis test on the level of determinants of the variables X and Y with simple regression, the data analysis test tool used SPSS version 25, with a population of 60 respondents with the saturated sampling technique used in this study. The instrument in this study used interviews, observations and questionnaires as primary and secondary data. From the results of statistical calculations, the number for work coordination is 0.388, which means that it has a weak effect, in the sense that work coordination has less effect on employee performance. while for communication, it has a fairly strong influence, namely 0.767, which means it has a fairly strong influence, while work ethics gives a figure of 0.740, while for work coordination, communication, and work ethics together, it gives the highest value, which is 0.803. means jointly providing a very strong influence to improve employee performance.